Producción y reproducción de codornices (Coturnix Coturnix japónica) utilizando gallinas nodrizas. - Talledo Murillo, Gabriela Margarita (2011)
This research was conducted in the Province of Esmeraldas, Canton Rioverde Chontaduro Parish, on the farm owned Rancho Los Ficus family Talledo Murillo, whose geographical location is 10 ° 5 '25 "north latitude and 58 º 18' 36" South longitude at a height of 12 meters. Lasted 60 days, the objectives a) To determine the production and reproduction of quail using, chicken nurses, runes Creole, Creole fine, b) Assess the birth rate of quails, chickens used in the incubation nurses, c) Determine productive parameters using incubation quails, chickens nurses, d) Evaluate the costs of treatments, factors that were used in the present investigation. Factor A, Hens native nurses, nurses Gallinas finas. Factor B, 25, 30, quail eggs, 540 was used quail eggs, in phase two animals born with 381cotupollos experimental unit in which variables were measured using the 20% production for sampling, we used a completely randomized design (DCA) under factorial two races and 25, 30, 35 quail eggs to determine differences between means of treatments. Test was used Tukey's multiple range., Experimental measurements, Weight Loss (g), Fertility (%), Eggs, fertile hatching (%), contamination of eggs (%), hatchability of eggs (%) , Birth Rate (%), weight control, weight gain, food conversion, food consumption, mortality% The fertility outcome of quail eggs incubation with runes fine hens reported the 95.00 - 95.56%, the number of eggs per animal nurses incubation with chickens does not affect the high fertility rate range of 95.00 to presenting 95.83%. hatchability of hens runes, reached 85.89%, the highest percentage of hatchability and birth was introduced by using 35 eggs per animal with 81.50% and 75.93%. the best birth rate was highest in hens runes with 74.74%, the interaction of runes chickens and 30 quail eggs was the best birth to 80%, hatching quail eggs with hens and runes fine nurses does not affect productive performance gain weight, feed intake, feed conversion and mortality. In the incubation stage as the highest price recorded on T3 with $ 34.55 and the best return the T6 reported $ 2.45, and in the fattening stage total costs amount to $ 259.12 in 230 quail evaluated and the benefit cost is $ 2.66.